2016
DOI: 10.1016/j.freeradbiomed.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic inhibition of mitochondrial reactive oxygen species with mito-TEMPO reduces diabetic cardiomyopathy

Abstract: Aims The mitochondria are important sources of reactive oxygen species (ROS) in the heart. Mitochondrial ROS production has been implicated in the pathogenesis of diabetic cardiomyopathy, suggesting that therapeutic strategies specifically targeting mitochondrial ROS may have benefit in this disease. We investigated the therapeutic effects of mitochondria-targeted antioxidant mito-TEMPO on diabetic cardiomyopathy. Methods The mitochondria-targeted antioxidant mito-TEMPO was administrated after diabetes onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(172 citation statements)
references
References 52 publications
(60 reference statements)
8
151
1
4
Order By: Relevance
“…Essentially, the results were comparable to those we obtained with DHR123 (Fig 4A and 4B vs. 4E and 4F). Furthermore, we repeated these experiments in the presence of the mitochondria-targeted antioxidant MitoTEMPO [40]. MitoTEMPO abolished H 2 O 2 -induced ROS production in all groups (Fig 4E and 4F) indicating mitochondrial localization of the BGP-sensitive ROS production.…”
Section: Resultsmentioning
confidence: 98%
“…Essentially, the results were comparable to those we obtained with DHR123 (Fig 4A and 4B vs. 4E and 4F). Furthermore, we repeated these experiments in the presence of the mitochondria-targeted antioxidant MitoTEMPO [40]. MitoTEMPO abolished H 2 O 2 -induced ROS production in all groups (Fig 4E and 4F) indicating mitochondrial localization of the BGP-sensitive ROS production.…”
Section: Resultsmentioning
confidence: 98%
“…Nonetheless, a recent randomised CHF trial (Q-SYMBIO) indicated that CoQ 10 reduced cardiovascular end-points,41 highlighting potential therapeutic application, although no studies have specifically focused on diabetes. Other preclinical approaches targeting mitochondrial ROS include mitoTEMPO, a superoxide dismutase mimetic directed against mitochondria, which improves systolic/diastolic function in diabetic cardiomyopathy and reduces NADPH oxidase expression,42 although this has not been trialled in patients. Of potential ROS targets, Nox are perhaps most exciting given their specificity of signalling, although current preclinical inhibitors (eg, apocynin, VAS2870) remain non-selective for individual isoforms.…”
Section: Therapeutic Targeting Of Ros Signalling In Diabetesmentioning
confidence: 99%
“…Compelling evidence demonstrates that the development of DCM is related to the induction of cardiac oxidative stress, as characterized by the production of ROS, leading to mitochondrial dysfunction, which in turn promotes cardiac oxidative stress [29,30]. Therefore, we investigated the effect of FGF21 deletion on the production of ROS and mitochondrial dysfunction in STZ/HFD-induced diabetic mice.…”
Section: Fgf21 Deficiency Exacerbates Cardiac Oxidative Stress Mitocmentioning
confidence: 99%